2001
DOI: 10.1152/ajpregu.2001.281.3.r760
|View full text |Cite
|
Sign up to set email alerts
|

Postexercise fat intake repletes intramyocellular lipids but no faster in trained than in sedentary subjects

Abstract: The hypotheses that postexercise replenishment of intramyocellular lipids (IMCL) is enhanced by endurance training and that it depends on fat intake were tested. Trained and untrained subjects exercised on a treadmill for 2 h at 50% peak oxygen consumption, reducing IMCL by 26-22%. During recovery, they were fed 55% (high fat) or 15% (low fat) lipid energy diets. Muscle substrate stores were estimated by (1)H (IMCL)- and (13)C (glycogen)-magnetic resonance spectroscopy in tibialis anterior muscle before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
136
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 130 publications
(158 citation statements)
references
References 45 publications
19
136
3
Order By: Relevance
“…However, it has also been found that high IMCL levels correlate with high insulin sensitivity if endurance-trained athletes are compared with healthy sedentary subjects (20). This paradox has been confirmed in biopsy studies (21) and initiated a study on the relation of anthropometric determinants, aerobic capacity, insulin sensitivity and IMCL levels in two different muscle groups (22).…”
Section: Relation Between Imcl Content and Insulin Sensitivitymentioning
confidence: 94%
See 3 more Smart Citations
“…However, it has also been found that high IMCL levels correlate with high insulin sensitivity if endurance-trained athletes are compared with healthy sedentary subjects (20). This paradox has been confirmed in biopsy studies (21) and initiated a study on the relation of anthropometric determinants, aerobic capacity, insulin sensitivity and IMCL levels in two different muscle groups (22).…”
Section: Relation Between Imcl Content and Insulin Sensitivitymentioning
confidence: 94%
“…Boesch et al (2) revealed a decrease of IMCL in one subject performing a mountain bike ride over 3 h at about 70% of VO 2max , for the first time using 1 H-MRS to demonstrate that IMCL are metabolized during this form of exercise. In the following years, numerous reports on reduced IMCL levels during exercise were published and reviewed (17,20,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). It became obvious that both exercise duration and intensity are important factors in determining the reduction of IMCL (39).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, reports have shown that repletion of the muscle triacylglycerol stores following exercise is dependent on the macronutrient composition of the diet. 28 In particular, a high fat diet (55% fat) leads to complete recovery of previously depleted muscle triacylglycerol stores at 30 h postexercise, while a low fat diet (15% fat) does not. The diet provided in our study was a moderate 30% fat, and perhaps not high enough to quickly replenish any previously utilized muscle triacylglycerol.…”
Section: Discussionmentioning
confidence: 99%